Price Appreciation, Bargaining Power, and the Determinants of Corporate Leasing Policy - Daniel John Stone (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2011)
This study uses price appreciation and bargaining power measures to determine whether current accounting standards are effective at classifying leases by ownership risk. I use a regression model, and find that there is a positive and significant relationship between changes in capital leases and my proxies for price appreciation and the interaction between price appreciation and bargaining power. I also find, however, that it’s possible that operating leases may be increasing faster, which would discount the theory that these standards are operating properly. These results should be cause for further study on the subject and should be interesting to regulators.
Keywords: Accounting; Leasing; Corporations